Mapping Experiences and Research about Unaccompanied Refugee Minors in Sweden and Other Countries - Aycan Celikaksoy; Eskil Wadensjö (Institute for the Study of Labor (IZA), 2016)
Many unaccompanied children have applied for asylum during the last few years, especially in 2015. These children face special challenges and risk being exploited due to their age and legal status. In this paper we survey research and otherwise documented experiences regarding this group of children. The main focus is on Sweden, the European country that has received most unaccompanied children but we also report on the experiences of other Nordic countries, a list of other EU member states, as well as USA and Turkey. We also try to summarize the main lessons for a policy to assist these children to integrate in the countries they have arrived to.
Keywords: F22; J13; J15; J61; 330; unaccompanied minors; separated refugee children; migration; reception policies; integration policies